2006
DOI: 10.1097/01.ana.0000181285.71597.e8
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Functional Neurosurgery

Abstract: The use of functional stereotactic neurosurgery is increasing for treatment of patients with movement disorders and other chronic illnesses. The anesthetic considerations include the influence of the anesthetic agents on the microelectrode recordings and stimulation testing of an awake patient. The purpose of this study was to review the anesthetic management and incidences of intraoperative complications during functional neurosurgery in our institution. One hundred seventy-eight patients underwent an ablativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 28 publications
0
53
1
2
Order By: Relevance
“…The process of electrodes' placement is guided by MERs and concomitant macrostimulation, which consists of intraoperative physical stimulus or mental tasks to assess the responses of patients to DBS [7]. Anesthetic drugs have an important impact at this stage of the surgery [7,8].…”
Section: Technique and Physiological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of electrodes' placement is guided by MERs and concomitant macrostimulation, which consists of intraoperative physical stimulus or mental tasks to assess the responses of patients to DBS [7]. Anesthetic drugs have an important impact at this stage of the surgery [7,8].…”
Section: Technique and Physiological Considerationsmentioning
confidence: 99%
“…Currently, limited data has been published with regards to the anesthetic management of DBS with no strict guidelines to follow by healthcare providers [8]. Nevertheless, there are some common concerns for DBS surgery, including patient comfort, Airway and blood pressure management , neuromonitoring, and anesthetic drugs interference with MERs.…”
Section: Anesthetic Considerations In Patients Undergoing Dbsmentioning
confidence: 99%
“…Though no clear data exists in regards to suggestions that 'awake' technique versus general anesthesia provides better MER signaling, studies have suggested that total intravenous techniques using combination of propofol and remifentanil may in fact lead to suppression of parkinsonian tremors. In addition, other options may include using 'twilight' or monitored anesthesia care with and without sedation, analgesia, or both [58][59][60][61].…”
Section: Summary Of Anesthetic Techniquesmentioning
confidence: 99%
“…This seems to be a relatively common occurrence when using propofol infusion for DBS procedures. Sneezing can cause patient discomfort, interfere with surgical mapping, and cause sudden rises in intracranial pressure putting patients at higher risks of intracranial hemorrhages, making it important to avoid intraoperatively [61][62][63][64][65][66].…”
Section: Summary Of Anesthetic Techniquesmentioning
confidence: 99%
“…16 Because the brain is free from pain fibers, the electrode insertion part of the procedure is performed with the patient awake while receiving monitored anesthesia care or an asleep-awake-asleep technique. 3,[10][11][12]14,21,22 However, young children with severe dystonia, developmental delay, and other associated cardiorespiratory conditions are not good candidates for awake procedures because their restlessness and anxiety can interfere with the operation. The unsedated patient may also have a higher risk of intracerebral bleeding from intraoperative hypertension.…”
mentioning
confidence: 99%